Subcellular proteomics of mice gastrocnemius and soleus muscles - vitorino, r (2007)
A proteomics characterization of mice soleus and gastrocnemius white portion skeletal muscles was performed using nuclear, mitochondrial/membrane, and cytosolic subcellular fractions. The proposed methodology allowed the elimination of the cytoskeleton proteins from the cytosolic fraction and of basic proteins from the nuclear fraction. The subsequent protein separation by two-dimensional gel electrophoresis prior to mass spectrometry analysis allowed the detection of more than 600 spots in each muscle. In the gastrocnemius muscle fractions, it was possible to identify 178 protein spots corresponding to 108 different proteins. In the soleus muscle fractions, 103 different proteins were identified from 253 positive spot identifications. A bulk of cytoskeleton proteins such as actin, myosin light chains, and troponin were identified in the nuclear fraction, whereas mainly metabolic enzymes were detected in the cytosolic fraction. Transcription factors and proteins associated with protein biosynthesis were identified in skeletal muscles for the first time by proteomics. In addition, proteins involved in the mitochondrial redox system, as well as stress proteins, were identified. Results confirm the potential of this methodology to study the differential expressions of contractile proteins and metabolic enzymes, essential for generating functional diversity of muscles and muscle fiber types.